The limit theorems for the sums of random variables related to a Markov chains. III - Statulevičius, V. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. А. Статулявичус. Предельные теоремы для сумм случайных величин, связанных в цепь Маркова. III V. Statulevičius. Ribinės teoremos atsitiktinių dydžių, surištų į Markovo grandinę sumoms. III